2023
DOI: 10.1002/ijgo.14668
|View full text |Cite
|
Sign up to set email alerts
|

Postvoid residual bladder volume after uncomplicated vaginal delivery

Abstract: Objective To create a reference curve for postvoid residual volume (PVRV) in asymptomatic postpartum women who are at low risk of developing postpartum urinary retention (PUR), a well‐known complication in the immediate postpartum period. Methods This is a prospective observational study measuring PVRV after uncomplicated vaginal delivery. PVRV was assessed by transabdominal ultrasound using a portable ultrasound scanner within the first 26 h after delivery (PVRV 1) and on the day of discharge (day 2 or 3 post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…This finding was supported by a study by Saraswathi et al (2019) who studied" Postpartum voiding dysfunction in vaginal delivery: Identify the Risk Factors " voiding problems could be attributed to urinary tract infection and pain. On the other hand, this finding contradicted with Degasper et al, (2023) who studied "Post void residual bladder volume after uncomplicated vaginal delivery". They found that longer duration of labor was the major risk factor.…”
Section: Discussionmentioning
confidence: 72%
“…This finding was supported by a study by Saraswathi et al (2019) who studied" Postpartum voiding dysfunction in vaginal delivery: Identify the Risk Factors " voiding problems could be attributed to urinary tract infection and pain. On the other hand, this finding contradicted with Degasper et al, (2023) who studied "Post void residual bladder volume after uncomplicated vaginal delivery". They found that longer duration of labor was the major risk factor.…”
Section: Discussionmentioning
confidence: 72%